Hacking connected cars : tactics, techniques, and procedures - Knight, Alissa (John Wiley & Sons, Inc., 2020)
Chapter 3 Threat Modeling -- STRIDE Model -- Threat Modeling Using STRIDE -- VAST -- PASTA -- Stage 1: Define the Business and Security Objectives -- Stage 2: Define the Technical Scope -- Stage 3: Decompose the Application -- Stage 4: Identify Threat Agents -- Stage 5: Identify the Vulnerabilities -- Stage 6: Enumerate the Exploits -- Stage 7: Perform Risk and Impact Analysis -- Summary -- Chapter 4 Vulnerability Analysis -- Passive and Active Analysis -- WiFi -- Bluetooth -- Summary -- Chapter 5 Exploitation -- Creating Your Rogue BTS -- Configuring NetworkinaPC